Positive correlation between maternal self-efficacy and the children’s oral hygiene behavior - Abdat, Munifah; Fitri, Dani Laulea; Al-Gunaid, Talat Hasan; Chairunas, Chairunas (Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Maternal self-efficacy is known to be a strong predictor of children’s oral hygiene behavior. Several studies have shown that the majority of children do not have good oral hygiene according to the OHI-S index, which is associated with parental concern for their oral hygiene. Mother’s self-efficacy in understanding their children’s oral hygiene needs influences tooth brushing habits. The aim of this study was to determine the correlation between maternal self-efficacy and children’s oral hygiene behavior in Aceh. Methods: This study employed a quasi-experimental design with 124 participants divided into 62 in the intervention group and 62 in the control group. The inclusion criteria were mothers with children aged 4-6 years. Maternal self-efficacy was assessed using a modified Self-Efficacy Scale for Maternal Oral care (SESMO) questionnaire. Children’s oral hygiene was measured by the Patient Hygiene Performance plaque index. Data analysis used Spearman correlation test (p<0.05). Results: This study showed that high maternal self-efficacy is associated with higher levels of maternal education (high school and college). Mothers in the intervention group predominantly reported good to moderate child oral hygiene compared with the control group. A significant correlation was found between maternal self-efficacy and child oral hygiene (r=0.352, p=0.001). Mothers with low self-efficacy had children with 3.10 times higher odds of having poor oral hygiene (OR=3.10; CI=95%; 1.07-8.98). Conclusion: Children’s oral hygiene behavior was positively correlated with maternal self-efficacy. The findings of this study suggest that mothers with low self-efficacy are at risk of having children 4-6 years with poor oral hygiene.Keywords: Maternal, self-efficacy, children, oral hygiene, plaque index